Maturity and Success in Projects from the Perspective if the Supplier and Customer Binomial - Rabechini Jr., Roque; Müller, Sandra; Racz, André; Silva, Alexandre Campos Pinto (Review of Business Management, 2010)
One of the concerns that have accompanied the attention of business management researchers and professionals is the effective relationship in the binomial supplier - customer. The secret of a successful relationship seems to be in the results of projects developed in that two-way route. Thus, the most successful the projects that travel in this route are, in theory, the better the relationship between the parties. However, knowing the exact project management capacity from both sides is a challenge that can help unravel the understanding of this phenomenon - characterized as a kind of maturity duet. To understand how tuned is this duet of maturity in information technology project management this work presents the results of a research in which 13 projects were analyzed, involving 5 companies under the binomial supplier - customer. The multiple cases study approach was chosen to obtain the assessment of the project management maturity considering the both internal factors (cost, time and performance) and external factors of success (utility, satisfaction and effectiveness). As a result it was possible to verify that the greater the supplier maturity, the greater the success perception in internal factors, and the greater the customer maturity, the greater the success perception in external factors. Key words: Project maturity. Sucess in projects. Managing projects competencies.